Studi Multi-Situs Kedisiplinan Anak Usia Dini Di TK Kota dan TK Desa - Anis Shofiyatul Izzah; Ahmad Samawi; Eny Nur Aisyah; Anis Shofiyatul Izzah; Ahmad Samawi (Universitas Negeri Malang, 2021)
Abstract: Attitudes and proper parenting from parents is an important capital for children's development later on. Attitudes, parenting parents and the circumstances surrounding the parents can have an influence on children's development. one of the basic moral development that must be instilled in children from an early age is discipline. Researchers used one of the case studies designs, namely multi-site studies, a qualitative research design involving several sites and research subjects as cases. This research is aimed at institutions located in cities and institutions located in villages. Data collection techniques using interviews, observation and documentation. Data analysis through the reduction stage, display data (data presentation) and conclusion drawing/verification. The results of the study found that in institutions in the village parents were rarely open about positive or negative things that children due to parents, this is very counter to what they should. This research is expected to be used as a comparison for future research on parental attitudes to each other open to the institution regarding the discipline of early childhood. Future researchers are also expected to add to the aspects studied in order to know the attitudes that must be done by parents and teachers to overcome disciplinary behavior in children. Abstrak: Sikap dan pola asuh yang tepat dari orangtua merupakan modal penting bagi perkembangan anak di kemudian hari. Sikap, pola asuh orangtua serta situasi dan kondisi yang sedang melingkupi orangtua dapat memberikan pengaruh terhadap perekembangan anak. salah satu dasar pengembangan moral yang harus ditanamkan dalam diri anak sejak usia dini adalah disiplin. Peneliti menggunakan salah satu desain studi kasus yaitu studi multi situs (multi-site studies), yaitu suatu rancangan penelitian kualitatif yang melibatkan beberapa situs dan subjek penelitian sebagai kasus. Penelitian ini ditujukan pada lembaga yang berada di kota dan lembaga yang berada di desa. Teknik pengumpulan data menggunakan wawancara, observasi dan dokumentasi. Analisis data melalui tahap reduksi, display data (penyajian data) dan conclusion drawing/verification. Hasil penelitian diketahui bahwa di lembaga yang berada di desa para orangtua jarang terbuka mengenai hal positif ataupun negatif yang dilakukan anak ke orangtua, hal ini kontra sekali dengan dengan yang seharusnya. Penelitian ini diharapkan dapat dijadikan perbandingan untuk penelitian selanjutnya tentang sikap orangtua untuk saling terbuka kepada pihak lembaga mengenai kedisiplinan anak usia dini. Peneliti selanjutnya juga diharapkan untuk menambah aspek yang diteliti agar mengetahui sikap-sikap yang harus dilakukan orangtua maupun guru untuk mengatasi perilaku disiplin pada anak.